2017
DOI: 10.1108/jkm-08-2016-0357
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating knowledge management through filtered big data: SME competitiveness in an agri-food sector

Abstract: Purpose-This paper aims to critique a facilitated knowledge management (KM) process that utilises filtered big data and, specifically, the process effectiveness in overcoming barriers to small and medium-sized enterprises' (SMEs') use of big data, the processes enablement of SME engagement with and use of big data and the process effect on SME competitiveness within an agri-food sector. Design/methodology/approach-From 300 participant firms, SME owner-managers representing seven longitudinal case studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 40 publications
2
94
0
Order By: Relevance
“…SMEs can exploit opportunities and overcome the liability of their small size by collaborating with external partners, such as customers, suppliers and other enterprises (Hanna & Walsh, ; Parida, Westerberg, & Frishammar, ). In this scenario, ICTs enable SMEs to break out of geographic and resource barriers, greatly enhancing long‐distance communication and knowledge sharing, accessing flows of knowledge and big data (O'Connor & Kelly, ). The hallmarks of new ICTs, which include rapid search, access, retrieval and exchange of information, make these technologies suitable for collaboration and knowledge sharing.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…SMEs can exploit opportunities and overcome the liability of their small size by collaborating with external partners, such as customers, suppliers and other enterprises (Hanna & Walsh, ; Parida, Westerberg, & Frishammar, ). In this scenario, ICTs enable SMEs to break out of geographic and resource barriers, greatly enhancing long‐distance communication and knowledge sharing, accessing flows of knowledge and big data (O'Connor & Kelly, ). The hallmarks of new ICTs, which include rapid search, access, retrieval and exchange of information, make these technologies suitable for collaboration and knowledge sharing.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…greatly enhancing long-distance communication and knowledge sharing, accessing flows of knowledge and big data(O'Connor & Kelly, 2017). The hallmarks of new ICTs, which include rapid search, access, retrieval and exchange of information, make these technologies suitable for collaboration and knowledge sharing.…”
mentioning
confidence: 99%
“…To date, small businesses have generally had limited exposure to such formalized sources of MI (Jocumsen, 2004;O'Connor and Kelly, 2017). However, MI resources are becoming increasingly more accessible to small businesses through funding from governmental bodies and technological aided delivery.…”
Section: Introductionmentioning
confidence: 99%
“…A review of literature suggests that there are a handful of studies available on agribusiness firms [7,8,5,9], with different sources of competitive advantage being proposed. Majority of the studies found human capital as source of competitive advantage of agribusiness sector.…”
Section: Introductionmentioning
confidence: 99%